The Effect of Oral Massage on Speech Delay in 2-3-Year-Old Toddlers - Rumlus , Maria Felisitas; Iswati, Retno Setyo; Hubaedah, Annah (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Speech delay in toddlers is a common developmental issue that can hinder communication and social interaction. If left unaddressed, this condition may create additional barriers to learning and social development. Therefore, early intervention is essential, particularly during the critical 2–3-year period. This study aimed to determine the effectiveness of oral massage in improving language development in toddlers with speech delay. The research was conducted at Ridha Therapy House, Sidoarjo, from January to March 2025 using a quantitative approach with a single-group pre-test–post-test design. A total of 17 toddlers were selected through total sampling. The intervention was administered twice weekly for six weeks, with each session lasting 20 minutes. The procedure involved external facial massage and intraoral stimulation following a standardized protocol, while language development was assessed using the CAT/CLAMS scale. The results showed an increase in mean language scores from 66.4 before intervention to 84.94 after treatment. Additionally, 57.1% of participants reached the